Comparison between paclitaxel-coated balloon and standard uncoated balloon in the treatment of femoropopliteal long lesions in diabetics. Issue 13 (March 2019) - Du, Xin; Wang, Feng; Wu, Dan-ming; Zhang, Min-hong; Jia, Xin; Zhang, Ji-wei; Zhuang, Bai-xi; Zhao, Yu; Guo, Ping-fan; Bi, Wei; Fu, Wei-guo; Guo, Wei; et al.
Abstract : Abstract: Atherosclerotic diseases may include femoropopliteal artery stenosis or occlusion. Percutaneous transluminal angioplasty (PTA) is an effective and minimally invasive treatment strategy for atherosclerotic femoropopliteal artery stenosis/occlusion disease. Balloon angioplasty is a widely used technique in the management of occlusive disease in almost all arterial segments. We enrolled 111 diabetics with long femoropopliteal lesions, among which 54 received PTA with paclitaxel-coated balloon (the Paclitaxel group), and 57 with standard balloon catheters (the Control group). The primary outcome was set as angiographic late lumen loss (LLL) within 6 months; the secondary angiographic outcome was binary restenosis. Clinical outcomes included Rutherford clarification, ankle-brachial index (ABI) and rate of clinically driven target lesion revascularization (TLR). Two groups had similar basal clinical features, angiographic and procedural characteristics. Compared to controls, the Paclitaxel group had a significantly lower 6-month LLL rate, 12-month binary restenosis rate, 12-month TLR, lower Rutherford grades at 3 and 6 months, and higher ABI at 3 months. For all factors which might influence outcomes, fasting blood glucose was negatively correlated with ABI; the blood urea nitrogen (BUN) was positively related with the Rutherford clarification grades. In addition, the coronary heart disease (CHD) and smoking histories were positively correlated with residual stenosis after treatment. Collectively, the paclitaxel-coated balloon angioplasty can yield more favorable angiographic and clinical outcomes than standard uncoated balloon angioplasty, even in the more challenging lesions (the long and occlusive femoropopliteal lesions) in diabetics, when it had a similar safety profile to the traditional balloon. Blood glucose, BUN, CHD, and smoking imply poor curative effects.